The role of the educational discourse in the process of training farmers in educational institutions of higher and professional education - Книш, І. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
The article discusses the phenomenon of educational discourse and its role in training farmers in educational institutions of higher and professional education. Thus, the author emphasizes that environmental education should reflect the continuity of the connection between society and nature, between the Humanities and the natural knowledge and become a process of acquisition, on the one hand, knowledge about the environment and about environmental problems, predicting their consequences, the need and possible solutions in case of occurrence. It is environmental education and environmental education specialists-farmers should go, according to the author, in two directions: theoretical knowledge about the environment and about the practical boundaries of human intervention into nature. The choice of the directions of the conceptualization of a new philosophical paradigm of education for professional agricultural workers, according to the author of the article suggests a solution to such problems: a new understanding of human nature, which is associated with the restructuring of the entire educational process and the humanization of educational practice; socio-cultural rethinking the relationships that arise between man and society, with a radical reassessment of the meaning of education as the inculcation of the individual in its socio-cultural surroundings and ontologization these relations through the recognition of their existential potential for each individual.